DOI: 10.31274/etd-180810-4976
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of feeding peroxidized oils on growth and oxidative status in swine and poultry

Abstract: important lipid peroxidation products that need to be measured as suggested by their consistent correlations with growth performance and oxidative status in swine and poultry. Additionally, these experiments and a review of literature indicate that markers of oxidative stress that should be measured include ISP and 8-OH-2dG in urine (pigs), and PC and GPx in blood (pigs and poultry). Overall, this thesis showed that oil quality should not be underestimated in livestock production. Feeding peroxidized oils can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In this study, ω3 enriched diet did not influence lipid peroxidation of sow plasma. It might be that the malondialdehyde measured in the TBARS test was absorbed quickly in the liver before being eliminated in urine without influencing TBARS levels in blood circulation [53]. Here, we observed that FRAP values of LR sows were similar at the end of gestation and tended to increase at the beginning of lactation, compared with CR sows.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, ω3 enriched diet did not influence lipid peroxidation of sow plasma. It might be that the malondialdehyde measured in the TBARS test was absorbed quickly in the liver before being eliminated in urine without influencing TBARS levels in blood circulation [53]. Here, we observed that FRAP values of LR sows were similar at the end of gestation and tended to increase at the beginning of lactation, compared with CR sows.…”
Section: Discussionmentioning
confidence: 48%
“…Storage of the oils inevitably results in lipid peroxidation, while consuming diets including peroxidized lipids leads to an impair-ment of body health. [27] Recently, natural products have been extensively performed to improve metabolism and health. Puerarin is a natural isoflavonoid and has been noted to have outstanding anti-inflammatory properties and strong antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Feed preparation and storage of the oils inevitably result in lipid peroxidation, while consuming diets including peroxidized oil leads to a decrease in growth and impairment of host health in poultry (Lindblom, 2017). It has been reported that natural products are extensively performed to promote the growth and health of poultry.…”
Section: Discussionmentioning
confidence: 99%